2018
DOI: 10.1016/j.clinthera.2018.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Self-reported Physical Activity and Skin Autofluorescence, a Marker of Tissue Accumulation of Advanced Glycation End Products in Adults With Type 1 Diabetes: A Cross-sectional Study

Abstract: Higher physical activity is related to lower accumulation of AGEs in patients with T1D. Our study provides new insight into the beneficial effects of physical activity in T1D according to tissue accumulation of AGEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…The skin concentrations of AGEs have been related to coronary calcifications, left ventricular masses and progression of intima-media thickness in the DCCT-EDIC study [ 11 ]. SAF was related to the age of the participants (ß = + 0.397; p < 0.001) which is very similar to reports from other groups in participants with T1D [ 26 28 ]. Although an indirect estimation of the accumulation of AGEs, SAF has some advantages on skin biopsies: low cost, simplicity, non-invasiveness, and repeatability.…”
Section: Discussionsupporting
confidence: 83%
“…The skin concentrations of AGEs have been related to coronary calcifications, left ventricular masses and progression of intima-media thickness in the DCCT-EDIC study [ 11 ]. SAF was related to the age of the participants (ß = + 0.397; p < 0.001) which is very similar to reports from other groups in participants with T1D [ 26 28 ]. Although an indirect estimation of the accumulation of AGEs, SAF has some advantages on skin biopsies: low cost, simplicity, non-invasiveness, and repeatability.…”
Section: Discussionsupporting
confidence: 83%
“…In fact, it was reported that the modification of the collagen such as advanced glycation end products (AGEs) contributed to the relationship between habitual physical activity and skin mechanical properties. Higher habitual physical activity was related to lower accumulation of AGEs in the skin of patients with type 1 diabetes using an AGE reader 9 . The autofluorescence measured using the AGE reader was positively correlated with the content of AGEs in the collagen of the skin 22 .…”
Section: Discussionmentioning
confidence: 89%
“…Regular moderate physical activity protected against oxidative damage, whereas endurance exercise with a lack of training mediated oxidative stress 8 . Higher habitual physical activity was related to lower accumulation of advanced glycation end products (AGEs) in patients with type 1 diabetes 9 . In addition, there are some reports regarding the relationship among physical activity skin structure and skin components 10 11 .…”
Section: | Introductionmentioning
confidence: 99%
“…In a second paper, Duda-Sobczak examines the potential for skin autofluorescence as a marker of tissue accumulation of advanced glycation end-products in adults with type 1 diabetes, to serve as a marker for physical activity among patients with type 1 diabetes. 11 Gastroparesis has been recognized as being associated with type 1 diabetes for many years but has only recently been shown to be fairly common among patients with type 2 diabetes. 12 Gastroparesis is defined as "a chronic symptomatic disorder of the stomach characterized by delayed emptying without evidence of mechanical obstruction."…”
Section: Emerging Diabetes Research From Early Investigatorsmentioning
confidence: 99%